(untitled) (Research, Society and Development, 2022)
The search for alternative materials that ensure adequate performance and reduction of environmental impacts, aiming to ensure our needs without compromising the survivability of future generations, is one of the biggest challenges today. Thus, this work aims to compare the effects of the incorporation of residues of different typologies in mortars, through the comparative method, which seeks to verify similarities and explain divergences between the samples evaluated. To perform the comparison, three studies from the same research group were selected and the results of the common trials were analyzed among the three studies: axial compressive strength (at 28 days), water absorption by capillarity, water absorption by immersion and void index. The result of the analysis showed that the typology of the residue and the substitution content can influence the physical and mechanical properties of the mixtures. Among the substitutions of the aggregate was the reduction in mechanical properties, however, there was better performance in the physical parameters of the mixtures. In relation to mortars with partial replacement of the binder, it was noticed that both for the mechanical parameters and for the physical parameters analyzed presented satisfactory results.